PENGARUH VARIASI WAKTU PANEN TERHADAP KADAR FLAVONOID TOTAL DAUN KUMIS KUCING (Orthosiphon aristatus (Blume) Miq.) - Yulia Widya Sari; Susilowati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Harvest time influences the formation of optimal active compound content in the areal parts in plant. It is known that differences in harvest time can affect the quality and quantity of traditional plant. Flavonoids are known to be active metabolites in Orthosiphon aristatus with a wide range of bioactivity. This research aims to determine the best harvest time for Orthosiphon aristatus leaves in order to obtain optimal simplicia quality. Plants were harvested in in the morning (06.00-07.00 WIB), in the afternoon (12.00-13.00 WIB) and in the evening (17.00-18.00 WIB). The picked leaves are then sorted, washed and dried using a drying oven before each simplicia is extracted. Extraction uses a maceration technique with 96% ethanol solvent. The simplicia and extracts obtained were analyzed for organoleptic, yield, drying loss and qualitative and quantitative analysis of total flavonoid compounds. Qualitative identification of flavonoids used dilute NaOH, Wilstater Cyanidin, and AlCl3 reagents, while for quantification total flavonoid levels were measured using UV-Vis spectrophotometry as Quercetin Equivalent. The difference in harvest time did not affect the organoleptic properties of leaves. The drying loss of simplicia meets the requirements in the Indonesian Herbal Pharmacopoeia Edition II (less than 10% w/w). The highest yield of simplicia (23.8% w/w) and extract (11.3% w/w) was produced during the harvest time of 12.00-13.00 WIB, followed by harvesting at 17.00-18.00 and 06.00-07.00 WIB. All extracts contain flavonoids, while the total flavonoid content in each extract showed significant differences. The highest total flavonoid content (4.423+0.029 mgQE/g extract) was related at the harvest time of 17.00-18.00 WIB and the lowest value (4.331+ 0.026 mgQE/g extract) was recorded at the harvest time of 06.00-07.00 WIB. Our findings in Orthosiphon aristatus, may pave the route towards the optimization of quality and quantity by selecting the best harvesting time of the plants.